2011
DOI: 10.1159/000329498
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Thymus in the Integrated Evolution of the Recombinase-Dependent Adaptive Immune Response and the Neuroendocrine System

Abstract: Before being able to react against infectious non-self-antigens, the immune system has to be educated in recognition and tolerance of neuroendocrine self-proteins. This sophisticated educational process takes place only in the thymus. The development of an autoimmune response directed to neuroendocrine glands has been shown to result from a thymus dysfunction in programming immunological self-tolerance to neuroendocrine-related antigens. This thymus dysfunction leads to a breakdown of immune homeostasis with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…When combined with complement and macrophages, IgM can stimulate complement and improve phagocytosis [78]. Regarding the immune system, T cells are associated with the cell-mediated response, whereas B cells are linked to the humoral response [79]. Antigen-stimulated T cells undergo a process of differentiation and transformation into plasma blasts, which release immunoglobulin and control immunological responses [80].…”
Section: Effects Of B Nigra Sprout Extract Administration On Immunogl...mentioning
confidence: 99%
“…When combined with complement and macrophages, IgM can stimulate complement and improve phagocytosis [78]. Regarding the immune system, T cells are associated with the cell-mediated response, whereas B cells are linked to the humoral response [79]. Antigen-stimulated T cells undergo a process of differentiation and transformation into plasma blasts, which release immunoglobulin and control immunological responses [80].…”
Section: Effects Of B Nigra Sprout Extract Administration On Immunogl...mentioning
confidence: 99%
“…It is reported that a numerous neuroendocrine self-antigens are expressed by the thymic epithelium which is controlled by the autoimmune regulator (AIRE) gene/protein. [ 18 ] According to a review, numerous gens are expressed in the thymus, including circulatory, central nervous, digestive, and eyes. [ 19 ] Myelin basic protein (MBP) is the second most abundant protein after proteolipid protein (PLP) in CNS.…”
Section: Mmunological C Haracteristicsmentioning
confidence: 99%